2017
DOI: 10.1007/s00894-017-3278-z
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the orientational versatility of steroid substrates—a docking and molecular dynamics study of a steroid receptor and steroid monooxygenase

Abstract: Numerous steroids are essential plant, animal, and human hormones. The medical and industrial applications of these hormones require the identification of new synthetic routes, including biotransformations. The metabolic fate of a steroid can be complicated; it may be transformed into a variety of substituted derivatives. This may be because a steroid molecule can adopt several possible orientations in the binding pocket of a receptor or an enzyme. The present study, based on docking and molecular dynamics, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…For reference, we also docked the ligand from the crystal structure of the sbAvd-2 (I117Y)–progesterone complex [PDB:5LUR] back into the ligand-binding site and, even in this case, the docking produced varying poses dissimilar to the ligand observed in the crystal structure, indicating the challenge of docking progesterone into Avd-like binding pockets. Interestingly, Panek and coworkers [48] recently reported that progesterone docked into human mineralocorticoid receptor and bacterial monooxygenase in orientation (‘D-ring first’) different from that observed in the crystal structures of these proteins (“A-ring first”).…”
Section: Resultsmentioning
confidence: 97%
“…For reference, we also docked the ligand from the crystal structure of the sbAvd-2 (I117Y)–progesterone complex [PDB:5LUR] back into the ligand-binding site and, even in this case, the docking produced varying poses dissimilar to the ligand observed in the crystal structure, indicating the challenge of docking progesterone into Avd-like binding pockets. Interestingly, Panek and coworkers [48] recently reported that progesterone docked into human mineralocorticoid receptor and bacterial monooxygenase in orientation (‘D-ring first’) different from that observed in the crystal structures of these proteins (“A-ring first”).…”
Section: Resultsmentioning
confidence: 97%
“…Microbial BVMOs have considerably broad substrate scope, for example the PockeMO can oxidize both a and d rings of the steroidal substrates [ 26 ], and this versatility is related to the structure of substrate binding pocket, able to accept bulky substrates in diverse configurations [ 26 , 27 ]. Such an idea of configurational flexibility of steroid substrates was proposed already in 1967 on the basis of diverse metabolic fates of steroids biotransformed by Aspergillus tamarii cultures [ 28 ].…”
Section: Introductionmentioning
confidence: 99%